2015
DOI: 10.1111/bcp.12619
|View full text |Cite
|
Sign up to set email alerts
|

Adverse effects reported in the use of gastroesophageal reflux disease treatments in children: a 10 years literature review

Abstract: Gastroesophageal reflux (GER) is commonly observed in children, particularly during the first year of life. Pharmacological therapy is mostly reserved for symptomatic infants diagnosed with GER disease (GERD), usually as defined in a recent consensus statement. The purpose of the present article was to review the reported adverse effects of pharmacological agents used in the treatment of paediatric GERD. We conducted this review using the electronic journal database Pubmed and Cochrane database systematic revi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
64
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(72 citation statements)
references
References 75 publications
0
64
0
5
Order By: Relevance
“…One review of children up to 18 years of age reported that at least 23% of patients treated with histamine receptor 2 antagonists experienced side effects, as did 34% of those treated with proton pump inhibitors 32. Concerns have been raised with regard to the impact of proton pump inhibitors on the gut microbiome and the association between using proton pump inhibitors and small bowel bacterial overgrowth in children 33, 34.…”
Section: Pharmacological Management Of Fgids In Early Lifementioning
confidence: 99%
“…One review of children up to 18 years of age reported that at least 23% of patients treated with histamine receptor 2 antagonists experienced side effects, as did 34% of those treated with proton pump inhibitors 32. Concerns have been raised with regard to the impact of proton pump inhibitors on the gut microbiome and the association between using proton pump inhibitors and small bowel bacterial overgrowth in children 33, 34.…”
Section: Pharmacological Management Of Fgids In Early Lifementioning
confidence: 99%
“…A recent review by Cohen et al 12 reported adverse effects in 34% of children treated with PPIs, including most commonly headaches, nausea, diarrhoea and constipation. Additionally, prolonged use of PPIs has raised concerns about hypochlorhydria and hypergastrinaemia, increased risk of infections, vitamin and mineral deficiencies, adverse bone health, food allergy and drug interactions.…”
Section: Toxicity Profiles Of Ppi In Childrenmentioning
confidence: 99%
“…There is increasing evidence that gastric acid suppression may place susceptible infants and children, particularly those with indwelling catheters or defective immune systems, at risk for nosocomial infections 12. Safety studies on the use of histamine-2 receptor antagonists (H2RAs) particularly in neonatal intensive care with hospital-acquired pathogens raised the following concerns: these gastric acid inhibitors in neonatal intensive care have been identified as a risk factor for necrotising enterocolitis,13 sepsis and meningitis,14 and bloodstream infections with Candida species 15 16.…”
Section: Toxicity Profiles Of Ppi In Childrenmentioning
confidence: 99%
“…To date, adverse effects have not been reported after 6 months of treatment with PPIs in patients with EoE; however, adverse effects have been reported in patients with a 10-year history of gastroesophageal reflux disease (GERD) [9] and are more frequent in GERD (34%) than in EoE (8.3%). Other adverse effects include visual alterations, especially blurred vision.…”
Section: Conflicts Of Interestmentioning
confidence: 99%